ENHO GENE EXPRESSION AND SERUM ADROPIN LEVEL IN RHEUMATOID ARTHRITIS AND SYSTEMIC LUPUS ERYTHEMATOSUS - Yolbas, S.; Kara, M.; Yildirim, A.; Gundogdu, B.; Kalayci, M.; Aydin, S.; Koca, S. S. (Bmj Publishing Group, 2014)
[Abstract Not Available]
15th Annual European Congress of Rheumatology (EULAR) -- JUN 11-14, 2014 -- Paris, FRANCE